2011
DOI: 10.3121/cmr.2011.1020.ps2-08
|View full text |Cite
|
Sign up to set email alerts
|

PS2-08: Adherence to Statins and Low-Density Lipoprotein Cholesterol Goal Attainment in Patients with Coronary Artery Disease

Abstract: 155HMORN -Selected Abstracts discussion of interventions, communication tools (e.g. written instructions from the physician, a home medication calendar with communication tools such as check boxes to indicate when a dose had been administered, and others) were high priority for parent participants. Conclusions: Parents can understand and perform an FMEA. The parent-team identified modifiable failure modes, many communication-related, which could lead to significant patient injury in home medication use. Parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Na primeira fase de análise desse estudo longitudinal, quando foram alocados somente pacientes de muito alto risco, o resultado foi semelhante, de 26,7% para 46,7% (STURZENEKER et al, 2023b). Em estudo transversal que envolveu 67.100 pacientes com DAC, níveis de LDL-C <70 mg/dl foram atingidos somente por 32,4% da amostra (CHI et al, 2014). Em nosso estudo, considerando a meta de LDL-C <70 mg/dl, que é preconizada para pacientes de alto risco, mesmo antes das ações do grupo multidisciplinar, o porcentual de indivíduos na meta era de 43% e após as ações aumentou para 57%.…”
Section: Discussionunclassified
“…Na primeira fase de análise desse estudo longitudinal, quando foram alocados somente pacientes de muito alto risco, o resultado foi semelhante, de 26,7% para 46,7% (STURZENEKER et al, 2023b). Em estudo transversal que envolveu 67.100 pacientes com DAC, níveis de LDL-C <70 mg/dl foram atingidos somente por 32,4% da amostra (CHI et al, 2014). Em nosso estudo, considerando a meta de LDL-C <70 mg/dl, que é preconizada para pacientes de alto risco, mesmo antes das ações do grupo multidisciplinar, o porcentual de indivíduos na meta era de 43% e após as ações aumentou para 57%.…”
Section: Discussionunclassified
“…Parris et al found that patients with dyslipidemia and diabetes mellitus who attained the target of LDL cholesterol level would have a higher medication adherence than patients who did not achieve (78) . Additionally, the study conducted by Chi et al to evaluate the association between low-density lipoprotein (LDL) target achievement and statin medication adherence in coronary artery disease patients (80) . They displayed that adherence patients were more probably to achieve at goal of LDL-cholesterol level than nonadherent.…”
Section: Cholesterol Levelmentioning
confidence: 99%